Modelling and Extraction of Current Harmonic Components based on Instantaneous Power Theory for Shunt Active Filter under Weak Grid - Farzad Sajadi; Mohammad Pichan; Adel Zakipour (مجله مدل سازی در مهندسی)
The most important part in the suitable performance of the active power filter is possible by precise harmonic extraction of load current. Current harmonic extraction is possible in both time and frequency domain. However, time domain methods have higher speed and low complexity. One of the most popular methods in this field is the Instantaneous Power Theory method but, the main problem is when the grid voltage is not ideal. Therefore, this paper provides a method based on the Instantaneous Power Theory that shows very good performance with the least complexity of implementation in all grid voltage states, whether asymmetry, distorted, or both at the same time. To examine the performance of the proposed method, the three -phase filtration is simulated in the MATLAB/Simulink environment under different grid voltage conditions and finally the experimental results are provided in the laboratory environment. The results verify the effectiveness of the proposed method where the THD% is decreased from 25% to 5%..